Firm Productivity and the Foreign-Market Entry Decision - Horst Raff; Michael Ryan; Frank Stähler (Kiel University, Department of Economics, 2008)
We use Japanese firm-level data to examine how a firm?s productivity affects its choice of foreign-market entry strategy. We study a sequence of decisions, starting with the choice between exporting and foreign direct investment (FDI). In the case of FDI, the firm faces two options: greenfield investment or merger and acquisition (M&A). If it selects greenfield investment, it has two ownership choices: whole ownership or a joint venture. Controlling for industry- and country-specific characteristics, we find that the more productive a firm is, the more likely it is to choose FDI rather than exporting, greenfield investment rather than M&A, and whole ownership rather than a joint venture. We also find that the assumed sequence of decisions fits the data better than alternative specifications.
Keywords: F15; F12; 330; Foreign direct investment; merger and acquisition; joint venture; greenfield investment; firm heterogeneity; productivity; Internationale Markteintrittsstrategie; Direktinvestition; Unternehmen; Produktivität; Japan